2022
DOI: 10.1111/jcmm.17474
|View full text |Cite
|
Sign up to set email alerts
|

MgIG exerts therapeutic effects on crizotinib‐induced hepatotoxicity by limiting ROS‐mediated autophagy and pyroptosis

Abstract: Crizotinib (CRIZO) has been widely employed to treat non‐small‐cell lung cancer. However, hepatic inflammatory injury is the major toxicity of CRIZO, which limits its clinical application, and the underlying mechanism of CRIZO‐induced hepatotoxicity has not been fully explored. Herein, we used cell counting kit‐8 assay and flow cytometry to detect CRIZO‐induced cytotoxicity on human hepatocytes (HL‐7702). CRIZO significantly reduced the survival rate of hepatocytes in a dose‐dependent manner. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Miltirone, a derivative of phenanthrene-quinone isolated from the root of Salvia miltiorrhiza Bunge, promotes the accumulation of intracellular ROS and induces the GSDME-dependent pyroptosis of HCC [ 158 ]. Likewise, crizotinib (CRIZO) increases ROS in HL-7702 cells to promote pyroptosis and inhibit HCC [ 159 ]. Furthermore, CRIZO induces apoptosis and suppresses the proliferation of HCC cells by inhibiting the phosphorylation of the anaplastic lymphoma kinase (ALK), Akt, and ERK [ 160 ].…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Miltirone, a derivative of phenanthrene-quinone isolated from the root of Salvia miltiorrhiza Bunge, promotes the accumulation of intracellular ROS and induces the GSDME-dependent pyroptosis of HCC [ 158 ]. Likewise, crizotinib (CRIZO) increases ROS in HL-7702 cells to promote pyroptosis and inhibit HCC [ 159 ]. Furthermore, CRIZO induces apoptosis and suppresses the proliferation of HCC cells by inhibiting the phosphorylation of the anaplastic lymphoma kinase (ALK), Akt, and ERK [ 160 ].…”
Section: Pyroptosis and Cancermentioning
confidence: 99%
“…Accumulates the ROS in cancer cells [159] Inhibits the activation of ALK, Akt, and ERK [160] Cannabidiol Regulates the caspase-3/GSDME pathway [161] Arrests the G0/G1 phase in the cell cycle and induces mitochondrial-dependent apoptosis [162] Metformin Promots FOXO3 expression and activates NLRP3 transcription [163] Regulates AMPK/p53/p38/miR-23a/FOXA1 pathway, regulates PI3K/Akt/ mTOR pathway, and downregulates Bcl-2 [164][165][166][167] Curcumin Increases the generation and accumulation of ROS [168] Promotes the P53-dependent apoptosis and inhibits the PI3K/Akt/GSK-3β…”
Section: Hepatic Carcinoma Crizotinibmentioning
confidence: 99%
“… 3 Previous studies have shown that crizotinib activates the oxidative stress response and stimulates hepatocyte mitochondrial apoptosis through reactive oxygen species (ROS) and the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway in human hepatocytes 10 and that accumulation of ROS promotes pyroptosis and excessive autophagy. 11 Further studies are needed to clarify the mechanism of crizotinib-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…GA is widely considered one of the main active substances of licorice and possesses a strong liver protective effect ( Yang et al, 2017 ; Wu et al, 2021b ). Li et al (2022) found that magnesium isoglycyrrhizinate exerts therapeutic effects on crizotinib-induced hepatotoxicity by decreasing the level of ROS. Xu et al (2022) also reported that GA significantly mitigated Sunitinib-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%